MATHEMATICS MIDDLE SCHOOL

Robert says his better long jump was about 1 foot farther than mays better long jump is he correct Mays jumps : 4 2/3 and 4 3/4

Robert jumps : 6 1/12 and 5 2/3​

Answers

Answer 1
Answer:

Answer:

No Robert is not correct because his better long jump was 1.33 foot farther than May's better long jump.

Step-by-step explanation:

Mays jumps

(i)

=>

=>

=>4.667

(ii)

=>

=>

=>4.75

May's better long jump is

Robert jumps :

(i)

=>

=>

=>6.08

(ii)

=>

=>

=> 5.66

Robert's better long jump is

Now the difference between Robert's better long jump and May's better long jump is

=>

=>

=>

=>6.08 - 4.75

=> 1.33


Related Questions

MIDDLE SCHOOL

What is the mixed number of

Answers

The answer is 3 and 2/5
MIDDLE SCHOOL

I have a Question What is? -34 x 89 + 9

Answers

-34 x 89 + 9

first multiply

-3026 +9

-3017

Answer:

-3017

Step-by-step explanation:

-34*89=-3026

-3026+9

HIGH SCHOOL

The measure of one of the acute angles in a right triangle is five times the measure of the other acute angle. what is the measure of the smaller acute angle?

Answers

he measure of the smaller acute angle in a right triangle is 15 degrees.

  • Let the bigger angle be a.
  • Let the smaller angle be b.

To find the measure of the smaller acute angle:

Translating the word problem into an algebraic expression, we have;

In Trigonometry, a right triangle is a triangle that has the sum of its interior angles equal to ninety (90) degrees.

Mathematically, this is given by the formula:

Smaller angle, b = 15 degrees.

Read more: brainly.com/question/14930619

The measure of the smaller angle is 15°
MIDDLE SCHOOL

I really need help please. Find the distance between the two points in simplest radical form. (−9,−4) and (0,−7)?

Answers

Answer:

 = 3sqrt(10)

Step-by-step explanation:

The distance between two points is found by

d =sqrt( x2-x1)^2 + (y2-y1)^2)

 = sqrt( 0--9)^2 +(-7--4)^2)

 = sqrt( (9)^2 + (-7+4)^2)

 = sqrt(9^2 + (-3)^2)

  = sqrt(81+9)

  = sqrt(90)

We know that sqrt(ab) = sqrt(a) sqrt(b)

  = sqrt(9) sqrt(10)

 = 3sqrt(10)

Random Questions